2019
DOI: 10.1038/s41598-019-47885-z
|View full text |Cite
|
Sign up to set email alerts
|

The droplet size of emulsion adjuvants has significant impact on their potency, due to differences in immune cell-recruitment and -activation

Abstract: Self-emulsification is routinely used for oral delivery of lipophilic drugs in vivo , with the emulsion forming in vivo . We modified this technique to prepare novel oil-in-water emulsions of varying droplet size and composition on bench to enable adjuvanted vaccine delivery. We used these formulations to show that smaller droplets (20 nm) were much less effective as adjuvants for an influenza vaccine in mice than the emulsion droplet size of commercial influenza v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…The results demonstrate the ability of Synthetic Biology-derived triterpene oils, of high purity and of nonanimal origin, to perform statistically as well in an O/W adjuvant formulation when compared to the current source of squalene using standard immunological markers for this type of adjuvant/vaccine study (i.e. IgG1, IgG2a, total IgG, and HI titers) 23,[43][44][45] . In both physiochemical and immunogenic properties, the Synthetic Biology produced squalene, botryococcene and methylated squalene performed equivalent to shark-derived squalene based on immunological activity.…”
Section: Discussionmentioning
confidence: 76%
“…The results demonstrate the ability of Synthetic Biology-derived triterpene oils, of high purity and of nonanimal origin, to perform statistically as well in an O/W adjuvant formulation when compared to the current source of squalene using standard immunological markers for this type of adjuvant/vaccine study (i.e. IgG1, IgG2a, total IgG, and HI titers) 23,[43][44][45] . In both physiochemical and immunogenic properties, the Synthetic Biology produced squalene, botryococcene and methylated squalene performed equivalent to shark-derived squalene based on immunological activity.…”
Section: Discussionmentioning
confidence: 76%
“…The exact mode of action of alum is still investigated and includes multiple pathways [ 35 ]: the presentation of the antigen on an alum particle improves the interaction with APCs; alum itself can interact with lipids on APCs membrane, activating the cells, and alum activates inflammasome, resulting into activation of innate immunity. Alternatively, oil-in-water emulsions (e.g., MF59) do not directly interact with APCs but modify the immune contexture surrounding the administration spot facilitating the migration of APCs [ 36 ]. The size of the emulsion droplet is of the utmost importance for the efficacy of the vaccination; too small particles have lower efficacy than 160 nm droplets [ 36 ].…”
Section: Past: Conventional Vaccine Formulationsmentioning
confidence: 99%
“…Contrastingly, nanoemulsions with smaller droplet size are inferior adjuvants, but with better safety profile (64). In the study of Shah et al (66) it was highlighted that there was no benefit in reducing nanoemulsion droplet size below 160 nm -both for humoral and cellular immune response. Taken all together -efficacy and safety profile of nanoemulsion-based adjuvants, their stability and possibility to undergo sterile filtration, it may be concluded that "smaller is not always the better".…”
Section: Physicochemical Properties Of Nanoemulsion-based Adjuvantsmentioning
confidence: 99%